Removing Organic Residues Using Backside Brush Scrubber Clean. (11th September 2015) - Chauhan, Kripa Nidhan; Sih, Vincent; Bhat, Talapady; Kang, Min Hyo; Kabutoya, Eiji; Cheng, Gordon
Abstract : In 2X nm devices, high-k metal gate have become an essential part of emerging devices. Wet cleaning plays an important part of advanced semiconductor manufacturing process. As the technology node advances, it has become more and more challenging. Presence of organic residues and cluster of particles on product wafers can cause lot of issues. These clusters of particles and organic residues are found to be die killers and hence, reduce the yield of the product. In this work, we will focus on root cause finding for the organic residue and clusters. The proposed solution demonstrates the improvement of 11X and yield gain of 3.5% as compare to product wafers, and cost savings for HVM (high volume manufacturing).